LOYALITAS PELANGGAN PADA PERUSAHAAN FREIGHT FORWARDING - Sabatini, Lidya Nurlita; Ardiana, I Made; Prasetya, Oce (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2016)
The objective of this study is to determine the influence of service quality and brand images to customer satisfaction and its impact on customer loyalty in PT Freight Solution Indonusa. The research population is all the customers export and import 200 customers. Number of sample is using Slovin formula 133 customers. The data obtained and collected through the instrument by a questionnaire using a Likert scale. The data, then analyzed using path analysis. The results of the calculation and the test data can be concluded that quality of service and brand image influenced on customer satisfaction and have an impact on customer loyalty. Therfore, the quality of service and a good brand image will create customer satisfaction and enhance customer loyalty.